PENGARUH MODEL DISCOVERY LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA PESERTA DIDIK KELAS XI SMA NEGERI 1 BUKITTINGGI - Belvianda, Nevin (Jurnal Edukasi dan Penelitian Matematika, 2023)
Mathematical problem solving is one of the mathematical abilities that must be mastered by students as stated in Permendikbud No. 58 of 2014. However, in reality the mathematical problem solving abilities of students at SMA Negeri 1 Bukittinggi are still not optimal. One reason is students who tend to be passive in learning. This resulted in student learning outcomes are also low. Therefore, a study was conducted by applying the discovery learning model to improve students' mathematical problem solving abilities. The purpose of this study was to find out and describe whether the mathematical problem solving abilities of students who learn using the discovery learning model are better than students who learn using conventional learning models in class XI SMA Negeri 1 Bukittinggi.This type of research is a quasi-experimental research with a research design that is static group design. The population of this study were students of class XI at SMA Negeri 1 Bukittinggi with the research sample being class XI IPS 1 as the experimental class and class XI IPS 3 as the control class. The sampling technique used is simple random sampling, where each member of the population has the same opportunity to be sampled. The research instrument used is the final test of solving mathematical problems.Based on data analysis using U Mann Whitney with a significance level of 0.05, a  is obtained, which is smaller than α = 0.05, which means that H0 is rejected. Then, after analyzing the results of the final problem solving test, the average value of the experimental class was higher than the average value of the control class. Thus it can be concluded that the mathematical problem solving abilities of students who learn using the discovery learning model are better than students who learn using conventional learning in class XI SMA Negeri 1 Bukittinggi.Keywords–Learning Model, Discovery Learning, Problem Solving